Evaluating impact of school outreach vaccination programme in Hong Kong influenza season 2018 - 2019 - Yu Lung Lau; Wilfred Hing Sang Wong; Sonal R. Hattangdi-Haridas; Chun Bong Chow (Taylor & Francis Group, 2020)
School-based vaccination, as a means to mitigate seasonal influenza outbreak, depends on attaining adequate coverage rate. We evaluated the potential of a fully subsidized school outreach vaccination (SOV) program to achieve epidemic prevention potential in Hong Kong. The purpose of this study was to evaluate the impact of SOV program 2018-2019 on influenza vaccination rates and influenza-like illness (ILI) in the primary school students and their household members during the influenza season. The vaccination rate was significantly higher in the schools offering SOV (intervention schools) (69.2% vs. 34.3%) than those not offering SOV (control schools) (p < .0001). The ILI rate was significantly reduced from 14.1% among non-vaccinated to 7.7% among vaccinated students (p < .0001). Influenza vaccine effectiveness against ILI was 45.3%. The vaccination rates of the household members were the same in both intervention and control schools except in the sub-group of preschool household members with the intervention significantly higher than the control group (43.8% vs. 32%, p < .0001). SOV program significantly improved influenza vaccine coverage, and the vaccine reduced ILI incidence. Extension of SOV program to all primary schools as well as kindergartens in Hong Kong could achieve epidemic prevention potential and should be evaluated.